INDICATORS OF SYSTEM GLUTATHION IN RATS WITH ALLERGIC DERMATITIS - Bereznyakova, A.I.; Jemela, O.D.; Cheremisina, V.F. (World of Medicine and Biology, 2015)
In the article presents the results of the dynamics of the glutathione system in rats with allergic dermatitis. It was established that one of the main attractions in the regulation of antioxidant defense in the dermis and epidermis takes in inflammation enzyme glutathione redox system. A significant decrease of reduced glutathione in serum in rats with allergic dermatitis due to insufficient activity of specific enzymes glutathione system, providing recovery of oxidized glutathione and refill the pool because of this reduced glutathione in the blood. In the treatment of allergic dermatitis appropriate than specific treatments, add antioxidants.
Keywords: alergic dermatitis; glutathione system; the restored glutathіone; the oxidized glutathіone; glutathіone peroxidase; glutathіone reductase; glutathіone transferase